Synthesis and aggregation behaviour of single-chain, 1, 32-alkyl-branched bis(phosphocholines) – part 2: lateral chain length triggers self-assembling from sheets to fibres to vesicles. Issue 18 (29th April 2020) - Gruhle, Kai; Tuchtenhagen, Max; Müller, Sindy; Hause, Gerd; Meister, Annette; Drescher, Simon
Abstract : The synthesis of six single-chain, alkyl-branched bolalipids and first investigations of the lyotropic behaviour of these lipids are reported. Abstract : Six single-chain, 1, 32-alkyl-branched bis(phosphocholines) PC-C32(1, 32C m )-PC have been synthesized as model lipids for naturally occurring archaeal membrane lipids. The preparation of these bipolar amphiphiles bearing lateral alkyl chains of different lengths (C4–C15) was realized using a Cu-catalyzed Grignard bis-coupling reaction of various primary alkyl-branched bromides as side parts and a 1, 22-dibromide as the centre part. The aggregation behaviour of these bolalipids in water was initially investigated by differential scanning calorimetry and transmission electron microscopy. As a main result, the types of aggregates found and their stability upon heating were strongly connected to the length of the lateral alkyl chain of the bolalipid: short and long lateral chains led to lamellar structures, whereas side chains of medium length led to fibrous aggregates. In future, these bolalipids could be used to produce tailored and stabilized liposomes for oral drug delivery.